Analisis Potensi Likuifaksi Menggunakan Data CPT (Cone Penetration Test) di Teluk Bintuni Papua Barat - Himmatul Azizah; Ferry Fatnanta; Muhamad Yusa (Jurnal Teknologi dan Rekayasa Sipil, 2022)
West Papua is an eastern part of Indonesia that has great potential for earthquakes. Eastern Indonesia's seismic activity was triggered by geographical conditions in three major earthquake paths, namely the zone of the confluence of the Pacific and Papua New Guinea plates, the Sorong fault line and the Tarera – Aiduna fault (Naryanto, 2019). Bintuni Bay is one of the regencies in West Papua Province, located between the south coast of Bird's Head and the coast of the Onin Peninsula, facing the Seram Sea off the west coast of Papua. The sorong fault is one of the active faults (faults) of the earthquake source in the Bintuni Bay area (Ciptakarya.pu, 2002). Liquefaction is one of the failures in the soil structure that can occur due to cyclic loads or earthquake vibrations. Liquefaction is the event of the transformation of noncohesive soil material from solid to liquid properties due to an increase in pore water pressure in the soil cavity. The liquefaction potential was analyzed using the boulanger Idriss method (2014). This method compares the value of CSR (Cyclic Stress Ratio) with CRR (Cyclic Resistance Ratio). The factor of safety value (FS) is used as a limit for potential liquefaction or not. If FS > 1 indicates that the soil layer has no potential for liquefaction, whereas if FS < 1 indicates a potential soil layer of liquefaction. The results of the analysis showed that the magnitude of ≥ 5,6 Mw with soil acceleration (amax) ≥ 0,16 g has the potential to reduce liquefaction with very low to very high categories. Coastal areas have a higher liquefaction potential than land areas.